AGRONOMIC AND MORPHOLOGICAL CHARACTERIZATION OF LIPPIA (VERBENACEAE) SPECIES NATIVE FROM BRAZILIAN SEMIARID REGION - Oliveira, Ariana Reis Messias Fernandes de; Oliveira, Lenaldo Muniz; Pastore, José Floriano Barea; Silva, Tânia Regina dos Santos; Costa, Larissa Correa do Bonfim (REVISTA DE AGRICULTURA, 2017)
The genus Lippia L. is represented by several aromatic species, producing essential oils with biological activity, especially antimicrobial. The semiarid region of Bahia contains several Lippia species that could be economically exploited. This study aimed to characterize morphological and agronomic traits of four species of Lippia native of the semiarid region. The species were collected in a number of cities of the state of Bahia. The experimental design was performed in randomized blocks with four repetitions and four plants per repetition for each species. We conducted quantitative and qualitative morphological characterizations, and evaluated the characters of stem, leaf and inflorescence; in addition to the agronomic characterization, with the fresh and dry matter of inflorescences, we evaluated leaves and stem and essential oil content and yield. The results showed morphological differences between the species for all traits evaluated, except for the number of flowers per inflorescence. The agronomical characterization showed differences for all measured characters, and the species Lippia lasiocalycina was distinguished by the essential oil yield.